Induction of hepatic fibrosis in mice with schistosomiasis by extracellular microRNA-30 derived from Schistosoma japonicum eggs - Chen, Yang; Hu, Yuan; Zhou, Hao; Jiang, Nan; Wang, Yiluo; Zhang, Jing; Shen, Yujuan; Yu, Guoying; Cao, Jianping (Frontiers in Immunology, 2024)
Schistosomiasis is a zoonotic parasitic malady induced by the infestation of schistosomes, a genus of trematodes. In China, the main parasite is Schistosoma japonicum, which poses a significant threat to human health. MicroRNAs (miRNAs), which are short, endogenous, non-coding RNAs abundant in egg-derived exosomes, are crucial for modulating the immune responses of the host and orchestrating the pathophysiological mechanisms of the host. Although the exosomes secreted by S. japonicum contain abundant miRNAs, the specific roles of these miRNAs in the pathogenesis of schistosomiasis-induced hepatic fibrosis are yet to be comprehensively elucidated. The egg exosomes of S. japonicum secrete miRNA-30, a novel miRNA. This novel miRNA can activate hepatic stellate cells (HSCs), the main effector cells of hepatic fibrosis, in vitro, i.e., it significantly increases the fibrogenic factors Col1(α1), Col3(α1), and α-SMA at both mRNA and protein levels. In addition, miRNA-30 may activate HSCs by targeting the host RORA gene. In addition, in vivo experiments were conducted by administering a recombinant adeno-associated viral vector to modulate the expression levels of miRNA-30. The overexpression of miRNA-30 in healthy mice significantly elevated the expression of Col1(α1), Col3(α1), and α-SMA at both the transcriptomic and proteomic scales. This overexpression was coupled with a pronounced augmentation in the hepatic hydroxyproline content. Conversely, the in vivo silencing of miRNA-30 in infected mice was observed to induce a considerable reduction in the size of hepatic granulomas and areas of collagen deposition. Hence, in vivo modulation of miRNA-30 expression may play a pivotal role in ameliorating the severity of hepatic fibrosis in mice afflicted with S. japonica. The study results suggest that miRNA-30 may augment schistosomiasis-induced hepatic fibrosis through a probable interaction with the host RORA. Our study may improve the current theoretical framework regarding cross-species regulation by miRNAs of hepatic fibrosis in schistosomiasis. It proposes novel avenues for the prophylaxis and therapeutic intervention of S. japonicum-induced hepatic fibrosis.